Registry Studies Use Inconsistent Methods to Account for Patients Lost to Follow-up, and Rates of Patients LTFU Are High - Kalyan Vamshi Vemulapalli, B.Sc; Karadi Hari Sunil Kumar, M.B.B.S., M.Ch. Ortho., F.E.B.O.T., F.R.C.S.Ed. (Tr. & Orth.); Vikas Khanduja, M.A. (Cantab) (Elsevier, 2021)
Purpose: To determine methods described in the literature to account for patients lost to follow-up (LTFU) in registry studies and whether rates of patient LTFU are within acceptable margins. Methods: A scoping review, where a literature search is conducted for studies from 9 arthroscopy registries, was performed on EMBASE, MEDLINE, and the annual reports of each registry. Inclusion criteria included studies with information on patient-reported outcome measures and being based on 9 national registries identified. Exclusion criteria included review articles, conference abstracts, studies not based on registry data, and studies from regional, claims-based, or multicenter registries. Studies were then divided into categories based on method of LTFU analysis used. Results: Thirty-six articles were identified for the final analysis. Categories for LTFU analysis included dropout analyses (n = 10), referencing validation studies (n = 12), contacting nonresponders (n = 4), and sensitivity analyses (n = 1). Referencing validation studies was the most common method (n = 12). Majority (n = 35) of the studies exceeded the recommended maximum rates for LTFU. Conclusions: Registry studies use inconsistent methods to account for patient LTFU, and rates of patients LTFU are unacceptably high. Clinical Relevance: The impact of patients LTFU in studies related to arthroscopic intervention is unknown. A universal method for accounting for patient follow-up is needed.